Efficacy of intratympanic injection of dexamethasone in the treatment of subjective idiopathic tinnitus - Shetty, Sandeep; George, Ammu; Chandrashekar, Shilpa; Prakash, Bhadravathi Ganesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: To study the efficacy of intratympanic injection of dexamethasone in cases of subjective idiopathic tinnitus. Methods: Prospective interventional study at the Department of ENT, JSS Medical College and Hospital, Mysore, in which 45 patients diagnosed clinically as subjective idiopathic tinnitus, for a duration of 2 years from October 2016 were included in the study. The patients were subjected to 3 intratympanic injections of dexamethasone once in a week for 3 weeks. They received a 0.5 ml intratympanic injection of 4mg/ml dexamethasone solution. After topical anaesthesia, using a 2 ml syringe and a spinal needle no. 22, the assigned solution was administered under direct vision using an endoscope in the postero- inferior quadrant of the tympanic membrane. They were followed up at the end of 1 and 3 months from the last injection. Tinnitus handicap inventory was repeated during the follow up and was compared to the value at presentation. Results: There was a statistically significant improvement in the THI at the first follow up compared with the baseline THI. Whereas there was no statistically significant change in improvement rate from the 1st follow up to the 2nd follow up (p=0.7), however there is decrease in the improvement, which means the improvement is temporary, and starts reverting by the second visit to some extent. Conclusions: It was observed that the improvement in the tinnitus was for a short term after intratympanic injection of dexamethasone.